1942
DOI: 10.1084/jem.75.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Diabetogenic Action of the Hypophysis From Various Animals

Abstract: The r51e of the anterior portion of the hypophysis in the production or intensification of diabetes was discovered in this Institute in 1929 and 1930 and since then has been studied continuously. An abstract of this work up to 1935 was published by Houssay in 1936. Some of the extracts of anterior hypophysis in animals without hypophysis and pancreas and with mild diabetes, intensified the hyperglycemia and glycosuria to a degree exceeding the intensity of the diabetes associated with pancreatectomy alone. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1950
1950
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Formative work in the 1930s and 1940s by Houssay et al (64) and Long and Lukens (65) first described a role for glucocorticoids in the regulation of carbohydrate metabolism and the development of diabetes. Subsequently, Ingle (66,67) and Long (68) illustrated that glucocorticoids stimulate gluconeogenesis, inhibit glucose utilization, and cause insulin resistance.…”
Section: Metabolismmentioning
confidence: 99%
“…Formative work in the 1930s and 1940s by Houssay et al (64) and Long and Lukens (65) first described a role for glucocorticoids in the regulation of carbohydrate metabolism and the development of diabetes. Subsequently, Ingle (66,67) and Long (68) illustrated that glucocorticoids stimulate gluconeogenesis, inhibit glucose utilization, and cause insulin resistance.…”
Section: Metabolismmentioning
confidence: 99%
“…Dome (1943) demonstrated that anterior pituitary tissue (54 lobes each in two days) had no effect on the blood sugar of the unoperated toads but is very active in the depancreatized animals. The human hypophysis on the other hand, produced a diabetogenic action in the normal dog on daily doses of 1.26 mg/kg/ day for two days (Houssay et al 1942). I t appears that the absence of the diabetogenic action following administration of pituitary tissue in the snake under study as also in the toads investigated by Dosne may be due to the opposing action of the endogenously produced insulin in the intact pancreases of these animals.…”
Section: Discussionmentioning
confidence: 86%
“…It is well known that the pituitary hormones have a regulatory influence on the carbohydrate metabolism (Houssay 1936(Houssay , 1942Houssay et al 1942 andDe Bod0 andAltszuler 1958). Hypophysectomy alone is known to produce a fall in blood sugar level in most vertebrate species examined (Mahoney 1934;Soskin et al 1935;Russell 1936;Slome 1936;Foglia ,et al 1955;Miller and Wurster 1958;Houssaf andPenhos 1960 andRangneker andSabnis 1966 a &b ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cavallero (1953) and Abrams (1953) reported the proliferation and hyperfunction of pancreatic alpha cell by growth hormone administration"1),"). Houssay (1942) reported concerning the diabetogenic action of growth hormone upon alloxan diabetic animal and hyperglicemic factor on the normal animal, and Anselmino(1933) and Hofmann (1933)' ") reported the hypoglycemic factor and pancreaticotropic factor of growth hormone. Marks (1940) reported that the repeated administration of growth hormone increases the amount of insulin in pancreas islet and Anselmino showed the excitment effect on the islet, showing the increase of pancreatic islet in number and But Bryans (1952) denied the existence of such pancreaticotropic hormone, showing that after hypophysectomy the normal pancreatic islet did not show any shrinking").…”
Section: D) Pancreasmentioning
confidence: 99%